Controlling Defects in Continuous 2D GaS Films for High‐Performance Wavelength‐Tunable UV‐Discriminating Photodetectors. Issue 7 (1st January 2020) - Lu, Yang; Chen, Jun; Chen, Tongxin; Shu, Yu; Chang, Ren‐Jie; Sheng, Yuewen; Shautsova, Viktoryia; Mkhize, Nhlakanipho; Holdway, Philip; Bhaskaran, Harish; Warner, Jamie H.
Abstract: A chemical vapor deposition method is developed for thickness‐controlled (one to four layers), uniform, and continuous films of both defective gallium(II) sulfide (GaS): GaS0.87 and stoichiometric GaS. The unique degradation mechanism of GaS0.87 with X‐ray photoelectron spectroscopy and annular dark‐field scanning transmission electron microscopy is studied, and it is found that the poor stability and weak optical signal from GaS are strongly related to photo‐induced oxidation at defects. An enhanced stability of the stoichiometric GaS is demonstrated under laser and strong UV light, and by controlling defects in GaS, the photoresponse range can be changed from vis‐to‐UV to UV‐discriminating. The stoichiometric GaS is suitable for large‐scale, UV‐sensitive, high‐performance photodetector arrays for information encoding under large vis‐light noise, with short response time (<66 ms), excellent UV photoresponsivity (4.7 A W –1 for trilayer GaS), and 26‐times increase of signal‐to‐noise ratio compared with small‐bandgap 2D semiconductors. By comprehensive characterizations from atomic‐scale structures to large‐scale device performances in 2D semiconductors, the study provides insights into the role of defects, the importance of neglected material‐quality control, and how to enhance device performance, and both layer‐controlled defective GaS0.87 and stoichiometric GaS prove to be promising platforms for study of novel phenomena and new applications. Abstract : A chemical vapor deposition method is developed for controlling defects in gallium(II) sulfide (GaS), and their influence on the UV photosensing response in devices is elucidated. Defects in GaS act as sites of photoinduced oxidation and degradation. High‐quality GaS 2D films show uniform UV photodetector response and defect tuning enables selective UV sensing.